2015
DOI: 10.1007/s13197-015-1876-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oriental and yellow mustard flours as natural preservative against aflatoxins B1, B2, G1 and G2 production in wheat tortillas

Abstract: Reduction of the AFs produced by Aspergillus parasiticus CECT 2681 in wheat tortillas by isothiocyanates (ITCs) from oriental and yellow mustard flours was evaluated in this study. Polyethylene plastic bags were introduced with wheat tortillas contaminated with A. parasiticus and treated with 0, 0.1, 0.5 or 0.1 g of either oriental or yellow mustard flour added with 2 ml of water. The wheat tortillas were stored at room temperature during 1 month. The quantification of the AFs produced was analyzed by liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…For example, Ekanayake et al (2006) demonstrated that IsoGard, a product based on p-HBITC extracted from moistened ground white mustard seed, had antimicrobial activity against pathogenic and spoilage bacteria, including Escherichia coli, Staphylococcus aureus, Campylobacter jejuni, Pseudomonas aeruginosa, Salmonella enteritidis, Listeria monocytogenes, Shigella boydii, and Clostridium perfringens. Furthermore, Quiles et al (2015) investigated the potential of mustard-based botanicals to reduce aflatoxin contamination of wheat tortillas by Aspergillus parasiticus and observed that the gaseous allyl ITC from oriental mustard was more effective than p-HBITC from white mustard; however, substantial reduction in aflatoxin occurred with either treatment. Calmes et al (2015) studied the mechanisms by which ITCs could cause fungal cell death using Alternaria brassicicola as a model organism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ekanayake et al (2006) demonstrated that IsoGard, a product based on p-HBITC extracted from moistened ground white mustard seed, had antimicrobial activity against pathogenic and spoilage bacteria, including Escherichia coli, Staphylococcus aureus, Campylobacter jejuni, Pseudomonas aeruginosa, Salmonella enteritidis, Listeria monocytogenes, Shigella boydii, and Clostridium perfringens. Furthermore, Quiles et al (2015) investigated the potential of mustard-based botanicals to reduce aflatoxin contamination of wheat tortillas by Aspergillus parasiticus and observed that the gaseous allyl ITC from oriental mustard was more effective than p-HBITC from white mustard; however, substantial reduction in aflatoxin occurred with either treatment. Calmes et al (2015) studied the mechanisms by which ITCs could cause fungal cell death using Alternaria brassicicola as a model organism.…”
Section: Discussionmentioning
confidence: 99%
“…These are inactivated during the baking process; however, fungal spoilage of bread and bakery products can still occur in the post-baking storage and or processing of bakery products. Rape seed oil or mustard flour have been evaluated in bread production to minimize fungal spoilage [16], the major active glucosinolates in rape seed brown mustard (Brassica juncea) oil are AITC (85%) and butenyl isothiocyanate (10%) [13] and these have broad fungicidal activity (Figure 3). In the bakery environment, 2 ppm AITC inhibited the growth of Penicillium roqueforti, P. corylophilum, Eurotium repens, A. flavus and Endomyces fibuliger on rye bread stored in an airtight environment [17].…”
Section: The Natural Anti-microbial Activity Of Glucosinolate Rich Foodsmentioning
confidence: 99%
“…Additional studies showed that gaseous AITC, benzyl, and phenyl isothiocyanate inhibited the growth of different fungal species and the production of mycotoxins in in vitro studies and food products [ 136 , 137 , 138 ]. Similar effects, starting from flours of oriental and yellow mustard, were obtained for wheat tortillas as preservatives against aflatoxins B1, B2, G1, and G2 [ 139 ]. Numerous data reported in the scientific literature encourage the use of GSLs to develop new formulations for the sustainable protection of crops from abiotic stresses, and a similar strategy can be imagined also for other cereals crops.…”
Section: Biocompounds In Brassicaceaementioning
confidence: 67%